Analysis of Musyarakah and Mudharabah Financing Against the Smoothness of Financing in Indonesian Syariah Banks - versiandika yudha pratama; amalina zulfa; ela agelia (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2025)
The purpose of this study is to examine how profit-sharing financing, namely mudharabah and musharakah financing, affects the smooth financing as determined by the Non-Performing Financing (NPF) of Islamic financial institutions. The data used in this study were examined using a multiple linear regression model. According to the findings of the study, mudharabah financing and NPF are positively correlated, meaning that the more mudharabah financing offered, the higher the chance of problematic financing. However, this relationship is not statistically significant, suggesting that the smoothness of money flow may be more influenced by variables outside the model. However, there is a negative correlation between musharakah financing and NPF, which shows that the increase in musharakah financing tends to reduce the risk of non-performing financing. Nevertheless, this effect also did not reach statistical significance The conclusion of this study is that, despite having a pattern of connections that align with Islamic financial theory, there are no funding options that significantly affect NPF in this model.